THE CHALLENGES AND IMPACT OF THE FINANCIAL SYSTEM ON ECONOMIC GROWTH IN THE CONTEXT OF THE INDIAN ECONOMY - Yadav, Sameer; Singh, Saurabh; Singh, Sanjay Kumar; Singh, Vibhu Prakash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the intricate relationship between the financial system and economic growth in India, focusing on the challenges and potential impact of the financial sector on sustainable development. As one of the world’s fastest-growing economies, India faces unique financial challenges, including financial inclusion, regulatory concerns, digital transformation, and evolving macroeconomic conditions. The study analyzes the role of financial intermediaries, banking reforms, and capital markets in fostering economic growth, alongside systemic risks such as non-performing assets (NPAs) and currency volatility. By leveraging data from the Reserve Bank of India (RBI) and economic indicators, the paper highlights the dynamic role of the financial sector as a growth enabler, as well as the structural and policy challenges that could impede progress. Through a review of existing literature and empirical evidence, the study aims to contribute to a nuanced understanding of how India’s financial system can better support inclusive and stable economic growth.